Analisa Peningkatan Pelanggan Pasang Baru di Pelayanan Teknis Barat PDAM Surabaya Menggunakan Metode SOAR - Floresta Andriano De Hautsmand; Joumil Aidil Saifuddin (Universitas 45 Surabaya, 2024)
PDAM Surya Sembada Kota Surabaya is a regional company (BUMD) that focuses on clean water services in the Surabaya area. Therefore, service must be improved more, especially in the Western Technical Services department, where to improve customer service, new installations are carried out analysis. The method used to analyze improvements in new installation services is using the SOAR method. The SOAR method is a method used to strengthen organizations both internally and externally. Then, using the SOAR method, an IFE value of 3.7 and an EFE value of 3.02 is obtained, then these values ​​are entered into cell I with a green index. This value shows that the West Technical Services Department is in a developing position at this time, especially in new installation services which are experiencing an increase. With this situation, it is hoped that the Western Technical Services department can maintain what has been achieved to date. And it is hoped that we can improvise to strengthen what has been built.